1991
DOI: 10.1039/ft9918701433
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AlPO4-14 by magic-angle-spinning nuclear magnetic resonance spectroscopy and thermoanalytical and adsorption measurements

Abstract: AIP0,-14 has been prepared using piperidine as templating agent. Uniform crystals of tabular habit were obtained. By thermoanalytical measurements of the as-synthesized sample t h e content of occluded piperidine was determined and its degradation was followed. From the 31P MAS NMR spectra it follows that there should exist at least three non-equivalent sites in t h e framework of calcined AIP0,-14. Completely reversible changes in t h e "AI and 31P M A S N M R spectra were found in dehydration/hydration cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 11 publications
3
61
0
Order By: Relevance
“…To prepare calcineddehydrated AlPO-14, either as-synthesized material was heated in air for 3 hours at 600 1C. The materials were determined to be phase pure by XRD, with the data being consistent with either the structure elucidated by Broach et al 21,22 (ipa-and calcined-dehydrated or in qualitative agreement with those presented by Zibrowius et al 3 (pip-AlPO-14).…”
Section: Synthesis and Characterizationsupporting
confidence: 75%
See 2 more Smart Citations
“…To prepare calcineddehydrated AlPO-14, either as-synthesized material was heated in air for 3 hours at 600 1C. The materials were determined to be phase pure by XRD, with the data being consistent with either the structure elucidated by Broach et al 21,22 (ipa-and calcined-dehydrated or in qualitative agreement with those presented by Zibrowius et al 3 (pip-AlPO-14).…”
Section: Synthesis and Characterizationsupporting
confidence: 75%
“…In addition to isopropylamine, AlPO-14 can also be synthesized with piperidine as the template molecule (pip-AlPO-14) and an early NMR study was performed by Zibrowius et al 3 The exact structure of pip-AlPO-14, the number of template molecules in the unit cell, and the ionic state of the template are not known. 3 The 27 Al and 31 P MAS NMR spectra of pip-AlPO-14 are shown in Fig. 2e and f.…”
Section: Nmr Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reversible structural transformation of this kind has not been reported previously for zeolites, but it is well known for other microporous materials, such as the zeotype AlPO 4 . [50] Chemisorption of the Lewis-type base Py on the activated NiHEU is apparently associated with coordination processes affording relevant Ni 2 coordination compounds throughout the crystals of the material (intra-zeolite and surface complexes). The powder XRD patterns of NiHEU-Py/R (Figure 8) demonstrated that the crystal structure of the zeolite is essentially preserved during dehydration/activation followed by Py sorption and rehydration.…”
Section: Definition Of Acid Sites In Nickel-loaded Heu-type Zeolitementioning
confidence: 99%
“…In addition, aluminum orthophosphates, AlPO , and modified products are characterized by solid-state NMR with respect to their catalytic properties (4)(5)(6)(7). In this paper we present a complete single-crystal X-ray structure determination of KAl with phosphate solution as described above.…”
Section: Introductionmentioning
confidence: 99%